Arabidopsis thaliana 2, 3‐bisphosphoglycerate‐independent phosphoglycerate mutase 2 activity requires serine 82 phosphorylation. (22nd August 2021) - Duminil, Pauline; Davanture, Marlène; Oury, Céline; Boex‐Fontvieille, Edouard; Tcherkez, Guillaume; Zivy, Michel; Hodges, Michael; Glab, Nathalie
SUMMARY: Phosphoglycerate mutases (PGAMs) catalyse the reversible isomerisation of 3‐phosphoglycerate and 2‐phosphoglycerate, a step of glycolysis. PGAMs can be sub‐divided into 2, 3‐bisphosphoglycerate‐dependent (dPGAM) and ‐independent (iPGAM) enzymes. In plants, phosphoglycerate isomerisation is carried out by cytosolic iPGAM. Despite its crucial role in catabolism, little is known about post‐translational modifications of plant iPGAM. In Arabidopsis thaliana, phosphoproteomics analyses have previously identified an iPGAM phosphopeptide where serine 82 is phosphorylated. Here, we show that this phosphopeptide is less abundant in dark‐adapted compared to illuminated Arabidopsis leaves. In silico comparison of iPGAM protein sequences and 3D structural modelling of At iPGAM2 based on non‐plant iPGAM enzymes suggest a role for phosphorylated serine in the catalytic reaction mechanism. This is confirmed by the activity (or the lack thereof) of mutated recombinant Arabidopsis iPGAM2 forms, affected in different steps of the reaction mechanism. We thus propose that the occurrence of the S82‐phosphopeptide reflects iPGAM2 steady‐state catalysis. Based on this assumption, the metabolic consequences of a higher iPGAM activity in illuminated versus darkened leaves are discussed. Significance Statement: Serine 82 phosphorylation and dephosphorylation of Arabidopsis thaliana 2, 3‐bisphosphoglycerate‐independent phosphoglycerate mutase 2 are crucial steps of the catalytic mechanism. Under the assumption that S82‐phosphopeptide content reflects steady‐state catalysis, in planta leaf iPGAM activity is higher in the light than in the dark.